The pathophysiology of post traumatic epilepsy - P K Sahoo; K I Mathai; G V Ramdas; M N Swamy (The Indian Journal of Neurotrauma, 2007)
Posttraumatic epileptogenesis provides an opportunity for the clinician to study the phenomenon of seizurogenesis along with the process of apoptosis which is triggered by traumatic brain injury (TBI), there is a simultaneous effort at neuro regeneration, neo synaptogenesis and plasticity. The seat of maximal neuronal changes after TBI is the hypothalamus. This loss of hilar cell inhibition of the hypothalamus on the CA3 region of the dentate gyrus results in mossy fibre sprouting and an attempt at neo synaptogenesis. While neo synaptogenesis is associated with long term potentiation (memory), it can also result in seizurogenesis. Pharmacologic inhibition of epileptogenesis remains in the realm of experimental therapeutics, but is likely to replace conventional antiepileptic drugs in the preventive management of post traumatic seizure disorder.